Teaching Shakespeare - Edens, Walter (Book collections on Project MUSE., 1977)
Here is a rich variety of approaches to teaching Shakespeare, described by authors who are distinguished teachers and scholars. In setting forth their classroom techniques they otter critical insights as well as stimulating ideas for use by other teachers. Their suggestions range from different pairings of plays, provocative questions for discussion, and ways of reading aloud, to projects for class performances and even possibilities for teaching Shakespeare outside the classroom. The contributors share a concern for developing students' interests and skills beyond strict formal analysis. Co.